Uncertainty about Carbon Impact and the Willingness to Avoid CO₂ Emissions - Davide D. Pace; Taisuke Imai; Peter Schwardmann; Joël J. van der Weele (Osaka University, Institute of Social and Economic Research (ISER), 2023)
With a large representative survey (N = 1, 128), we document that consumers are very uncertain about the emissions associated with various actions, which may affect their willingness to reduce their carbon footprint. We experimentally test two channels for the behavioural impact of such uncertainty, namely risk aversion about the impact of mitigating actions and the formation of motivated beliefs about this impact. In two large online experiments (N = 2, 219), participants make incentivized trade-offs between personal gain and (uncertain) carbon impact. We find no evidence that uncertainty affects individual climate change mitigation efforts through risk aversion or motivated belief channels. The results suggest that reducing consumer uncertainty through information campaigns is not a policy panacea and that communicating scientific uncertainty around climate impact need not backfire.
Keywords: 330; Treibhausgas-Emissionen; Klimaschutz; Konsumentenverhalten; Theorie